Phenotypic spectrum of the recurrent TRPM3 p.(Val837Met) substitution in seven individuals with global developmental delay and hypotonia. Issue 6 (10th February 2022) - Lines, Matthew A.; Goldenberg, Paula; Wong, Ashley; Srivastava, Siddharth; Bayat, Allan; Hove, Hanne; Karstensen, Helena Gásdal; Anyane‐Yeboa, Kwame; Liao, Jun; Jiang, Nan; May, Alison; Guzman, Edwin; et al.
Abstract: TRPM3 encodes a transient receptor potential cation channel of the melastatin family, expressed in the central nervous system and in peripheral sensory neurons of the dorsal root ganglia. The recurrent substitution in TRPM3 : c.2509G>A, p.(Val837Met) has been associated with syndromic intellectual disability and seizures. In this report, we present the clinical and molecular features of seven previously unreported individuals, identified by exome sequencing, with the recurrent p.(Val837Met) variant and global developmental delay. Other shared clinical features included congenital hypotonia, dysmorphic facial features (broad forehead, deep‐set eyes, and down turned mouth), exotropia, and musculoskeletal issues (hip dysplasia, hip dislocation, scoliosis). Seizures were observed in two of seven individuals (febrile seizure in one and generalized tonic–clonic seizures with atonic drops in another), and epileptiform activity was observed in an additional two individuals. This report extends the number of affected individuals to 16 who are heterozygous for the de novo recurrent substitution p.(Val837Met). In contrast with the initial report, epilepsy was not a mandatory feature observed in this series. TRPM3 pathogenic variation should be considered in individuals with global developmental delays, moderate–severe intellectual disability with, or without, childhood‐onset epilepsy.